2023
DOI: 10.3847/1538-4357/acf37c
|View full text |Cite
|
Sign up to set email alerts
|

An Optically Discovered Outburst from XTE J1859+226

Eric C. Bellm,
Yuankun Wang,
Jan van Roestel
et al.

Abstract: Using the Zwicky Transient Facility, in 2021 February we identified the first known outburst of the black hole X-ray transient XTE J1859+226 since its discovery in 1999. The outburst was visible at X-ray, UV, and optical wavelengths for less than 20 days, substantially shorter than its full outburst of 320 days in 1999, and the observed peak luminosity was 2 orders of magnitude lower. Its peak bolometric luminosity was only 2 × 1035 erg s−1, implying an Eddington fraction of about 3 × 10−4. The source remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…We assume the X-ray outburst parameters are representative of the optical outbursts. However, there is evidence that short optical outbursts can happen without a state change or full X-ray brightening, such as in misfired or failed outbursts (e.g., Alabarta et al 2021;Baglio et al 2022;Bellm et al 2023) and possibly the outburst of Swift J1943+0228 reported in this paper. As a result, our cut here may be too stringent, as systems may undergo optical outbursts more frequently, particularly as activity without the substantial X-ray brightening needed to trigger X-ray monitors.…”
Section: Outbursting Lmxbsmentioning
confidence: 64%
See 3 more Smart Citations
“…We assume the X-ray outburst parameters are representative of the optical outbursts. However, there is evidence that short optical outbursts can happen without a state change or full X-ray brightening, such as in misfired or failed outbursts (e.g., Alabarta et al 2021;Baglio et al 2022;Bellm et al 2023) and possibly the outburst of Swift J1943+0228 reported in this paper. As a result, our cut here may be too stringent, as systems may undergo optical outbursts more frequently, particularly as activity without the substantial X-ray brightening needed to trigger X-ray monitors.…”
Section: Outbursting Lmxbsmentioning
confidence: 64%
“…Examples of lightcurves passing all cuts are given in Figure 5. After visual inspections and literature searches for lightcurves displaying characteristics of LMXB outbursting, we recovered three known LMXBs in the alert archives: XTE J1859+226 (ZTF21aagyzqr; Bellm 2021a; Bellm et al 2023), Swift J1911.2 +0036 (ZTF18accedau), and MAXI J1807+132 (ZTF19abvioim; Shidatsu et al 2019). One source from the live search, Swift J1911.2+0036, was also recovered in the archival search.…”
Section: Archival Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations